The colonial legacy of education: Evidence from Tunisia - Mhamed Ben Salah; Céderic Chambru; Maleke Fourati (African Economic History Network (AEHN), 2022)
We study the effect of exposure to colonial public primary education on contemporary education outcomes in Tunisia. We assemble a new data set on the location of schools with the number of pupils by origin, along with population data during the French protectorate (1881-1956). We match those with contemporary data on education at both district and individual level. We find that the exposure of local population to colonial public primary education has a long-lasting effect on educational outcomes, even when controlling for colonial investments in education. A one per cent increase in Tunisian enrolment rate in 1931 is associated with a 1.69 percentage pointsincrease in literacy rate in 2014. Our results are driven by older generations, namely individuals who attended primary schools before the 1989/91 education reform. We suggest that the efforts undertaken by the Tunisian government after independence to promote schooling finally paid off after 40 years and overturned the effects of history.
Keywords: D10; N37; N47; 330; Colonial investment; Primary education; Tunisia